SENGKETA INVESTASI ASING DI INDONESIA : ANALISIS KASUS NEWMONT DAN IMPLIKASI TERHADAP HUKUM INVESTASI NASIONAL - Daffa Ariefiano Satria (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The dispute between the Government of Indonesia and PT Newmont Nusa Tenggara reflects a major challenge in managing foreign investment within the national mining sector. This study aims to conduct a juridical analysis of the share divestment conflict and its implications for the reform of Indonesia’s investment law. Using a normative juridical method with a statutory and case study approach, the research finds that the tension between the contract of work and national regulations has led to significant legal uncertainty. The international arbitration ruling strengthened Indonesia’s legal position, but also highlighted the need for a more consistent, transparent, and nationally aligned investment legal system. This study recommends the reformulation of investment policies and the strengthening of legal institutions to address future complexities in foreign investor relations.